Pengaruh Pengaruh Motivasi Belajar, Efikasi Diri, dan Komunikasi Interpersonal Guru terhadap Kinerja Akademik Siswa MAS Persiapan Negeri 04 Medan - Siregar, Nurjannah; Fadhli, Muhammad (Media Manajemen Pendidikan, 2025)
This study aims to comprehensively examine the influence of students’ motivation to learn, their self-efficacy, and teachers’ interpersonal communication skills on academic achievement, employing a quantitative correlational research design. The research population consisted of all 288 twelfth-grade students at MAS Persiapan Negeri 04 Medan, with a sample size of 167 students determined using Slovin’s formula at a 5% margin of error. Data were analyzed through descriptive statistics facilitated by Smart PLS 4 software. The results of the hypothesis testing indicated that the P-values for each independent variable were below the customary threshold of 0.05, which signifies a statistically significant positive effect on the dependent variable. Moreover, the collective influence of these independent variables was confirmed by a p-value of 0.000, further validating their joint impact, explaining approximately 70.8% of the variance in students’ academic performance. The remaining 29.2% of variance is attributable to other factors not accounted for within the scope of this study.